2013
DOI: 10.1093/aobpla/plt052
|View full text |Cite
|
Sign up to set email alerts
|

Conservative water management in the widespread conifer genus Callitris

Abstract: How plants manage their water use in seasonally dry environments is a major component of each individual species' ecology. We examined closely related species of a highly successful Australian conifer genus, Callitris, to determine whether species growing under contrasting climates showed adaptive specialization in the way they used water. Sampling 4 Callitris species growing across a large climatic range we found that each exhibited a similar strategy of linking growth very tightly with rainfall events, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(38 reference statements)
4
18
0
Order By: Relevance
“…In relation to precipitation, Brodribb et al . (, ) and Drew et al . (, ) have found that larger growth increments are less related to total precipitation over the wet season than to the frequency of rainfall events.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In relation to precipitation, Brodribb et al . (, ) and Drew et al . (, ) have found that larger growth increments are less related to total precipitation over the wet season than to the frequency of rainfall events.…”
Section: Discussionmentioning
confidence: 92%
“…One of the species in this genus, Callitris intratropica , distributed across much of monsoonal Australia, is extremely drought tolerant (Brodribb et al . , ), resilient to termite attack but sensitive to intense fire (Yates & Russell‐Smith ; Russell‐Smith ; Bowman et al . , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed meteorological data including air temperature and precipitation over the year for a nearby location are provided by Brodribb et al . (). Gunn Point is characterized by an immense seasonal variation in precipitation, with 85% of mean annual rainfall (∼1850 mm per year) falling in the wet season between November and March, and almost no rainfall between May and September (Cook & Heerdegen ).…”
Section: Methodsmentioning
confidence: 97%
“…Callitris as a genus, in general, has a very conservative water management strategy with an anisohydric (delayed closing) stomatal response to soil drying and is one of the most stress‐resistant tree genera known (Brodribb et al. ). In the investigated Callitris ‐species the rainforest associated C .…”
Section: Discussionmentioning
confidence: 99%